Preliminary Study: The Potential of the Nyalawean Tradition as a Form of Cultural Tourism in The South Coastal Waters of Sukabumi and Banten, Indonesia - Annida, Shafira Bilqis; Faqih Baihaqi (International Journal of Contemporary Sciences (IJCS), 2024)
Nyalawean is a tradition carried out by the people of the southern coast of Java, especially in Sukabumi and Banten Regencies. In practice, nyalawean is an activity in coastal communities that involves catching young fish around the coast and river estuaries in groups. This fishing activity often attracts local and foreign tourists enjoying the beautiful beaches. This research was conducted as a preliminary study that formulates the potential of the nyalawean tradition as a form of cultural tourism around the southern coastal waters of Java, Sukabumi and Banten Regencies. Literature studies and direct interview surveys were finished in April-August 2023. We found that young fish caught in the nyalawean procession were generally in the larval and juvenile stages. The results of direct interviews with 887 tourists showed 94.8% of tourists' enthusiasm for the nyalawean tradition. Most tourists consider nyalawean to be an exciting form of tradition to watch. Some even desired to catch and enjoy the processed fish larvae and juveniles they obtained. These findings show the high potential for the nyalawean tradition to be developed as a form of marine tourism on the southern coast of Java, Sukabumi and Banten Regencies